THE FACTORS PERFORMANCE OF FAMILY PLANNING OFFICERS WITH ACHIEVEMENT NUMBER OF NEW FAMILY PLANNING PARTICIPANTS LONG-TERM CONTRACEPTIVE METHODS IN TUBAN REGENCY 2017 - Nadya Kumalasari; Rinanti Rahayunig Bekti; Djazuly Chalidyanto (Universitas Airlangga, 2022)
Introduction: The target of new KB participants for the Long-Term Contraception Method (MKJP) that was not achieved and the decline in the achievement of the new KB MKJP is the responsibility of PKB. This is due to the role of PKB as the spearhead of the success of the family planning program in the field. The purpose of this study was to determine the factors of family planning counselor teamwork related to the achievements of the new MKJP family planning participants. Methods: This research is a descriptive quantitative study, using a cross-sectional design. Result: The results of this study found that 14 of the 20 PKB teams with good leadership teams experienced a low decline and the remaining six teams experienced a high decline. The category of decreasing participants is divided into two, namely the low decline is the team that has decreased from the previous year of 11.77% - 27.54%, while the high decline category is the team with a decrease from the previous year of 27.55% - 43.31%. Conclusion: This happens when the team implements mutual performance monitoring, backup behavior, adaptability, and loop communication properly, so the decrease in the achievement of new MKJP KB participants will be lower, and vice versa. When the workforce is able to work well together, by paying attention to the work of one team and trying to help each other in achieving the agreed goals, it will indirectly improve performance so that it will easily reach the target.